2013
DOI: 10.1002/joc.3728
|View full text |Cite
|
Sign up to set email alerts
|

A climatology of aerosol optical depth over China from recent 10 years of MODIS remote sensing data

Abstract: Using the recent 10-year (March 2000 to February 2010) MODIS data of aerosol optical depth (AOD), the distributions of annual and seasonal mean AOD over China are presented, and the trends and seasonal variations in AOD over 10 regions in China are analysed. The spatial pattern of annual mean AOD is characterized generally with two low centres and two high centres over China. Two low AOD centres are located in the areas with a high vegetation cover and a sparse population in (1) the high-latitude region in Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(97 citation statements)
references
References 43 publications
7
88
2
Order By: Relevance
“…It is noted that the BTH, PRD and YRD regions host three major urban clusters that constitute huge spatial sources of anthropogenic aerosols . This brief discussion clearly illustrates the seasonal variation of the AOD, as well as the regional differences in the seasonal variation as earlier shown by, e.g., Song et al (2009), Luo et al (2014 and Li et al (2017).…”
Section: Seasonal Variationsupporting
confidence: 69%
See 1 more Smart Citation
“…It is noted that the BTH, PRD and YRD regions host three major urban clusters that constitute huge spatial sources of anthropogenic aerosols . This brief discussion clearly illustrates the seasonal variation of the AOD, as well as the regional differences in the seasonal variation as earlier shown by, e.g., Song et al (2009), Luo et al (2014 and Li et al (2017).…”
Section: Seasonal Variationsupporting
confidence: 69%
“…Earlier studies on the aerosol climatology and trends over China were made using ground-based remote sensing, i.e., sun photometers in CARSNET , hand-held sun photometers in the Chinese Sun Hazemeter Network (CSHNET; Y. and solar radiation measurements (e.g., X. , or satellite data, in partic-ular MODIS (e.g., Li et al, 2003;Song et al, 2009;Luo et al, 2014;Tan et al, 2015;H. Xu et al, 2015;Ma et al, 2016; but also using multiple satellite data (Lin et al, 2010;Guo et al, 2011Guo et al, , 2016bDong et al, 2017;Zhao et al, 2017;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…3. Luo et al (2014) considered the value of AOD > 0.5 as the big value in China. However, in our data for more than half of eastern China, the frequency of AOD > 0.5 is larger than 50 % (Fig.…”
Section: Climatological Mean and Interannual Variationmentioning
confidence: 99%
“…Wu et al (2013) pointed out that MODIS data were usually valid throughout China and revealed the characteristics of aerosol transport and different extinction features in East Asia. Luo et al (2014) verified the good quality of MODIS AOD over land in China and used 10-year data to construct the climatology of AOD over China. Based on the previous validations, MODIS AOD data are considered to have good quality over China region and can capture the features of aerosol distribution.…”
Section: Pollution Datamentioning
confidence: 99%
“…Two MODIS onboard Terra and Aqua measure the earth system in multiple bands since 1999 and 2002, respectively. The Visible Infrared Imaging Radiometer Suite (VIIRS) that is onboard the National Polar-orbiting Partnership (Suomi-NPP) with similar device climatology [35,44]. These products have great potentials to serve air quality monitoring and research.…”
Section: Introductionmentioning
confidence: 99%